Valoração econômico-ecológica dos serviços ecossistêmicos na comunidade de Caetanos de Cima, Amontada/CE - Ferreira, Amanda dos Santos (2024)
Biodiversity and ecosystem services (BES) are declining, with serious consequences for human well-being and life on Earth. This research aims to assess the ecosystem services along the Ceará coastline, focusing on the community of Caetanos de Cima, Amontada/CE. The Ceará coastline provides services that promote socioeconomic development, such as artisanal fishing and community tourism. The methodology included identifying ecosystem services through literature review and participant observation, as well as classification according to the Common International Classification of Ecosystem Services (CICES). For economic-ecological valuation, an adaptation of the Estimated Reference Values for Environmental Benefits (VERB) was used. The results showed that the values of provisioning services (R$12,763,850.08), regulation (R$9,741,330.08), and cultural (R$12,889,788.24) resulted in an average VERB of R$35,394,968.58 per year, or R$2,949,580.71 per month. These figures highlight the economic importance of ecosystem services for the community, emphasizing the need for their valuation and conservation. Therefore, this model not only reinforces the significance of ecosystem services but also has the potential to stimulate public policies aimed at environmental conservation, contributing to the strengthening of local environmental management.